2014
DOI: 10.1016/j.biocon.2014.01.005
|View full text |Cite
|
Sign up to set email alerts
|

Impacts of alien grass invasion in coastal seed banks vary amongst native growth forms and dispersal strategies

Abstract: Impacts of alien grass invasion in coastal seed banks vary amongst native Impacts of alien grass invasion in coastal seed banks vary amongst native growth forms and dispersal strategies growth forms and dispersal strategies

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
14
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 16 publications
(14 citation statements)
references
References 62 publications
0
14
0
Order By: Relevance
“…In the case of S. secundatum , runner species (especially those with short‐distance dispersal capabilities) may require assisted reintroduction upon S. secundatum removal, through either the addition of propagules or seedlings, as this functional group is likely to exhibit more rapid species losses in response to invasion than either woody or tufted species. Furthermore, woody species, which are long lived and have a similar richness and density of soil‐stored propagules between S. secundatum ‐invaded and non‐invaded forest (Gooden and French ), may dominate regenerating vegetation following S. secundatum removal and suppress the recolonisation by herbaceous runners through pre‐empting available resources. Long term monitoring will be required to ensure that runner species gain sufficient representation in the regenerating standing vegetation following invader removal.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In the case of S. secundatum , runner species (especially those with short‐distance dispersal capabilities) may require assisted reintroduction upon S. secundatum removal, through either the addition of propagules or seedlings, as this functional group is likely to exhibit more rapid species losses in response to invasion than either woody or tufted species. Furthermore, woody species, which are long lived and have a similar richness and density of soil‐stored propagules between S. secundatum ‐invaded and non‐invaded forest (Gooden and French ), may dominate regenerating vegetation following S. secundatum removal and suppress the recolonisation by herbaceous runners through pre‐empting available resources. Long term monitoring will be required to ensure that runner species gain sufficient representation in the regenerating standing vegetation following invader removal.…”
Section: Discussionmentioning
confidence: 99%
“…At this stage, most of the native species were well‐established (mean ± SE % total vegetation cover per plot = 45.32 ± 1.92) and had reached reproductive maturity. Stenotaphrum secundatum plants were introduced as seedlings rather than seeds because during monitoring of plots positioned at the edges of large infestations we found that S. secundatum spread via the lateral proliferation of stolons and there was no seed present within the seed bank (Gooden and French , ). Seedlings were propagated from the ends of adventitious stolons collected from the leading edges of large infestations at two locations (34°22′46.40″S, 150°54′51.80″E; Puckeys Estate: 34° 24′25.20″S, 150°53′46.60″E; Primbee: 34°30′15.10″S, 150°52′25.10″E), and were planted randomly across each of the 16 mesocosms at a rate of 10 stolons per plot.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“… Ohga 1923 ). Propagules (seeds) can persist in the soil without any seedlings or adult plants being visible (see Thompson and Grime 1979 ; Holmes and Cowling 1997 a ; Gooden and French 2014 ). Furthermore, determining the presence or size of soil-stored seed banks is difficult, partly because they are so spatially heterogeneous ( Jones 1998 ) and/or transient (see Thompson and Grime 1979 ).…”
Section: Plant Life-history Traits: Seed Banks and Dormancymentioning
confidence: 99%
“…Low numbers of shrubs and trees were evident in seed banks from invaded and uninvaded sites, but as invaded sites may be the focus of restoration efforts in the near future, these areas are likely to be difficult to return to natural habitats. Large variation between seed bank and standing vegetation has been recorded in Australia (Mason et al ., ; Gooden & French, ) and overseas (Holmes & Cowling, ), although some uninvaded areas are more similar (Henderson et al ., ; Bekker et al ., ).…”
Section: Discussionmentioning
confidence: 99%